An Inscribed Stone with a Greek Inscription from Machaerus, Jordan - Ovadiah, Asher (Liber annuus, 2017)
A five-line Greek inscription, engraved on a soft irregular limestone, was found several decades ago in the Herodian fortress of Machaerus (Μαχαιροῦς) in Jordan. The script is somewhat careless and uneven, indicating the lack of a skilled hand. The inscription, attributed to the early Byzantine period, includes two proper names: a rare masculine Greek name, Ἀλέκιος, and a Greek transliteration of the common masculine Latin personal name Μᾶρκoς (Marcus). The emphasis on their virtues (ἀρεταί) and the Crux immissa suggest that they had undergone some kind of spiritual experience. It is unclear whether these two men had arrived at Herodian Machaerus from the neighbouring early Byzantine village of Machaberus, or they were hermits who had dwelt in caves at the foot of the fortress and in its surroundings.